National Assessment of Criminal Justice Needs, 1983: (United States) - Chabotar, Kent ([Verlag nicht ermittelbar], 1985)
In 1983, the National Institute of Justice sponsored a program evaluation survey by Abt Associates that was designed to identify the highest priority needs for management and operational improvements in the criminal justice system. Six groups were surveyed: judges and trial court administrators, corrections officials, public defenders, police, prosecutors, and probation/parole officials. Variables in this study include background information on the respondents' agencies, such as operating budget and number of employees, financial resources available to the agency, and technical assistance, research, and initiative programs used by the agency. The codebook includes the mailed questionnaire sent to each of the six groups in the study as well as a copy of the telephone interview guide.